BIBLIOMETRIC ANALYSIS OF THE WORLD SCIENTIFIC PRODUCTION IN CHEMICAL ENGINEERING DURING 2000-2011. PART 2: ANALYSIS OF THE 1,000 MOST CITED PUBLICATIONS - Esther García-carpintero; Ruben Miranda (Journal of Amasya University the Institute of Sciences and Technology)
A comprehensive bibliometric analysis of the scientific production of Chemical Engineering area has been carried out using the Web of Science database for the period 2000-2011 through three complementary studies. Part 2 demonstrated a displacement of the most cited publications to the Far East, especially due to China, however, this displacement is less important to that observed for total scientific production (Part 1). United States is still the country with the highest number of articles among the 1,000 most cited (31.5%), largely above what expected from their number of publications, followed by Germany (8.4%) and China (7.5%). The international collaboration, at least globally, seems not being an important issue for producing highly cited papers. In fact, only two from the top 25 most cited papers were international collaborations (8%). Furthermore, a large share of reviews among the 1,000 most cited papers (65%) has been observed. Although the number of institutions with more publications among the most cited in the area are from United States, the two institutions with the highest cited papers are CNRS (France) and CSIC (Spain). The most cited papers are highly concentrated in a few journals: around half of the most cited papers were published in five journals. Generally, the most cited papers are published in journals with high impact factors, however, there is also a significant number of highly cited papers published in journals with low or not having impact factor.